A new paradigm of Luca Pacioli’s bookkeeping on blockchain phenomenon - Suham Cahyono; Imran Haider; Tjiptohadi Sawarjuwono (Jurnal Akuntansi Aktual, 2023)
AbstractThe objective of this study is to examine the double and triple entry bookkeeping related to blockchain technology bookkeeping. The data we obtained for 30 articles from the database we searched for were provided by major publishers (Elsevier (www.sciencedirect.com), Emerald (www.emeraldinsight.com), Springer (www.springerlink.com), and Wiley (www. wiley.com)) and by service libraries (Complete Business Resources and Web of Science). We show the thoughts of philosopher Foucault regarding the power of knowledge, which will be associated with the phenomenon of the triple-entry and double-entry bookkeeping system paradigms. In addition, we document the blockchain technology has changed the paradigms of both bookkeeping systems. The novelty in this article is the implementation of the philosopher Foucault's thought in the paradigm of the triple-entry and double-entry bookkeeping systems. Our study contributes to expanding the existing literature by providing some arguments and findings regarding the blockchain bookkeeping systems and the future research agenda.AbstrakTujuan dari penelitian ini adalah untuk mengkaji pembukuan double dan triple-entry yang terkait dengan pembukuan teknologi blockchain. Data yang kami peroleh adalah 30 artikel dari database penerbit besar (Elsevier (www.sciencedirect.com), Emerald (www.emeraldinsight.com), Springer (www.springerlink.com), dan Wiley (www.wiley.com)) dan dari perpustakaan layanan (Sumber Daya Bisnis Lengkap dan Web of Science). Kami tunjukkan pemikiran filsuf Foucault mengenai kekuatan pengetahuan, yang akan dikaitkan dengan fenomena paradigma sistem pembukuan triple-entry dan double-entry. Selain itu, kami mendokumentasikan teknologi blockchain telah mengubah paradigma kedua sistem pembukuan tersebut. Kebaruan dalam artikel ini adalah implementasi pemikiran filsuf Foucault dalam paradigma sistem pembukuan triple-entry dan double-entry. Studi kami berkontribusi untuk memperluas literatur yang ada dengan memberikan beberapa argumen dan temuan mengenai sistem pembukuan blockchain dan agenda penelitian di masa depan.